Development of a textile antenna using a continuous substrate integrating the ground plane - Loss, Caroline (2019)
The exponential growth in the wearable market is boosting the industrialization process of manufacturing textile antennas. The patch of the printed antennas can be easily cut, embroidered or screen printed by machines. The conception of an optimal industrial substrate that meets all the mechanical and electromagnetic requirements is still a challenge. This paper presents a printed textile antenna for ISM band using a continuous Substrate Integrating the Ground Plane (SIGP). The SIGP is a novel textile material, which is a double fabric that integrates the dielectric substrate and the conductive ground plane in a single textile.